Pengaruh Work Life Balance Dan Job Burnout Terhadap Turnover Intention Melalui Job Satisfaction Sebagai Variabel Mediasi - putra, syauqy; Agus Seswandi; Donal Devi Amdanata (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2024)
The purpose of this research is to determine the influence of work life balance, job burnout and job satisfaction on turnover intention at PT. Mega Putri Graha Group and the role of job satisfaction in mediating the relationship between these variables. The method used in this research is descriptive quantitative with a survey approach via questionnaires. The population in this study were employees at PT. Mega Putri Graha Group with a sample size of 99 respondents. Statistical data analysis using the Smart PLS program. The results of this study indicate that work life balance has no effect on Turn over intention (Y) at PT. Mega Putri Graha Group. Meanwhile, Job Burnout and Job Satisfaction have a significant direct effect on Turn over intention at PT. Mega Putri Graha Group. Work life balance and Job Burnout have a significant effect on job satisfaction at PT. Mega Putri Graha Group. Based on the research results, it is known that Job Satisfaction is able to mediate the relationship between work life balance and job burnout on employee turnover intention at PT. Mega Putri Graha Group.